Assessment Of Angiosperm Plant Diversity Of Nijhum Dweep, Bangladesh - Uddin, Mohammad Zashim; Kibria, Md Golam; Hassan, Md Abul (Journal of the Asiatic Society of Bangladesh, Science, 2015)
The present article focuses the status of angiosperm plant diversity of Nijhum Dweep, a small Island in the Bay of Bengal close to Hatiya channel. From the analysis of the data a total of 152 plant species belonging to 56 families has been recorded. Among the recorded species, tree is represented by 66, shrub by 15, herbs by 58 and 13 by climbers. Of the species recorded from the area 51% species represented by 11 families and 49% represented by 45 families. Fabaceae appears to be largest in the Dicotyledones having 10 species whereas Poaceae is the largest in Monocotyledones having 12 species. Analysis confirmed that 68% of the recorded species found to be medicinal and 32% are used for other than medicinal purposes. Data analysis also showed that homesteads supported maximum plants followed by road side, cultivated land, mangrove and mangrove meadows. Collected data revealed that the occurrence of seven species namely Bruguiera gymnorrhiza, Diospyros blancoi, Derris trifoliata, Heliotropium curassavicum, Tamarix gallica, Typha elephentanea and Sarcolobus carinatus in the study area might be rare. Dolichandrone spathacea, a threatened of plant species of Bangladesh, was also found in this mangrove forest area. Through observations and discussion with local people, a number of threats to plant diversity have been identified. Finally, a number of possible conservation measures have been suggested for the management of angiosperm plant diversity of Nijhum Dweep. Asiat. Soc. Bangladesh, Sci. 41(1): 19-32, June 2015